Pengaruh Struktur Modal dan Efisiensi Bank terhadap Kinerja Keuangan pada Perusahaan Perbankan Konvensional - Alvido; Belliwati Kosim; Arradytia Permana; Veny Mayasari (MOTIVASI, 2025)
Purpose- This study aims to examine the effect of capital structure and banking efficiency on the financial performance of conventional banking companies listed on the Indonesia Stock Exchange (IDX). Design/methodology– This research uses a quantitative associative approach with secondary data obtained from the financial reports of 26 conventional banks during 2020–2024, resulting in 130 firm-year observations. Capital structure is measured by the Debt to Equity Ratio (DER), bank efficiency by the Operating Expenses to Operating Income ratio (BOPO), and financial performance by Return on Assets (ROA). Multiple linear regression is used for hypothesis testing. Findings- The results indicate that capital structure and bank efficiency simultaneously affect financial performance. Partially, DER has a positive and significant effect, while BOPO has a negative and significant effect on ROA. This implies that an optimal capital structure and efficient operational management can enhance profitability. The coefficient of determination (R²) of 0.911 shows that 91.1% of the variation in financial performance is explained by these two variables. The findings suggest that conventional banks need to manage debt and operational costs efficiently to maintain profitability and competitiveness.